2013
DOI: 10.1161/circimaging.112.000192
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Validation of Cardiovascular Magnetic Resonance Techniques for the Assessment of Myocardial Extracellular Volume

Abstract: Background-Extracellular matrix expansion is a key element of ventricular remodeling and a potential therapeutic target. Cardiovascular magnetic resonance (CMR) T 1 -mapping techniques are increasingly used to evaluate myocardial extracellular volume (ECV); however, the most widely applied methods are without histological validation. Our aim was to perform comprehensive validation of (1) dynamic-equilibrium CMR (DynEq-CMR), where ECV is quantified using hematocrit-adjusted myocardial and blood T 1 values measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
264
1
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 356 publications
(278 citation statements)
references
References 48 publications
8
264
1
5
Order By: Relevance
“…More importantly, they revealed abnormal T1 values in the remote, noninfarcted myocardium and a significant relationship with histologically determined collagen volume fraction, allowing an insight into the state of pathological remodeling in what was commonly considered as a normal reference. Later studies reiterated this relationship in patients with HF, [42][43][44][45] severe aortic stenosis, [46][47][48][49][50] and HCM 46 ( Table 3). Although these studies reported significant relationship with collagen volume fraction for all T1 indices, there is a considerable variation in the strengths of observed relationships.…”
Section: T1-mapping Indices: Initial Experience and Histological Corrmentioning
confidence: 94%
“…More importantly, they revealed abnormal T1 values in the remote, noninfarcted myocardium and a significant relationship with histologically determined collagen volume fraction, allowing an insight into the state of pathological remodeling in what was commonly considered as a normal reference. Later studies reiterated this relationship in patients with HF, [42][43][44][45] severe aortic stenosis, [46][47][48][49][50] and HCM 46 ( Table 3). Although these studies reported significant relationship with collagen volume fraction for all T1 indices, there is a considerable variation in the strengths of observed relationships.…”
Section: T1-mapping Indices: Initial Experience and Histological Corrmentioning
confidence: 94%
“…This leads to signal quantification of each myocardial voxel on a standardized scale with high resolution. ECV measurements also hold strong histological validation and closely correlate with collagen volume fraction [39]. ECV quantification by T1 mapping has significant prognostic implications.…”
Section: The Role Of T1 Mapping For Detection Of Diffuse Myocardial Fmentioning
confidence: 79%
“…ECV measurements have been shown to correlate closely with collagen volume fraction evaluated by quantitative histology. [26][27][28] In adult patients, elevated ECV has been associated with systemic hypertension, 29,30 ventricular arrhythmias, 31 ischemic injury, 32 myopathies, 33 and increased mortality rates. 34 shown that the presence and extent of LGE closely correlate with myocardial histology.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%